Histopathologic Analysis of CT-Guided Core Needle Biopsy in Radiologically Detected Suspicious Mediastinal and Lung Mass: Two Years’ Study in Tertiary Hospital - Rai, Ujwal; Sharma, Umesh Kumar; Yadav, Birendra Kumar (Medical Journal of Eastern Nepal, 2022)
Background: Pulmonary nodule ranges from infective to neoplastic lesion and thus at times remain diagnostic challenge for the management of patient. Therefore, proper diagnosis is very essential for appropriate treatment. Biopsy and FNAC plays important role in diagnosing these cases. After 2004 with establishment of therapeutic implication of distinguishing histologic subtypes of lung carcinoma with immunohistochemistry, lung biopsy has become inevitable even for molecular analysis as well. We studied our institution’s experience with percutaneous CT guided biopsy of lung nodules to determine the impact of this procedure in diagnosis of disease. Methods: This is hospital based descriptive study, of two years’ duration (March 2019 to April 2021), carried out at Department of Pathology, B&C Medical College Teaching Hospital and Research Centre Pvt. Ltd., Birtamode, Jhapa. Total 97 cases of CT guided biopsy were performed. Histopathologic analysis was performed and data were analyzed. Results: The most common malignancy diagnosed was Non-small cell carcinoma (NSCC), lung comprising 43.7% which required further immunohistochemistry testing for subcategorization. All infective cases were of Tuberculosis constituting 9.37% of all the cases. Benign cases were of mature cystic teratoma, thymoma and fibroma. Conclusions: Nowadays biopsy of lung in suspicious lesion is mandatory to establish diagnosis for appropriate management, moreover in malignancy cases for which most of the cases require immunohistochemistry and molecular analysis.